2016
DOI: 10.1002/smll.201602374
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion‐Activated Chemotherapeutic Function of Nanoparticulate Platinum as a Cisplatin Resistance‐Overcoming Prodrug with Limited Autophagy Induction

Abstract: Despite nanoparticulate platinum (nano-Pt) has been validated to be acting as a platinum-based prodrug for anticancer therapy, the key factor in controlling its cytotoxicity remains to be clarified. In this study, it is found that the corrosion susceptibility of nano-Pt can be triggered by inducing the oxidization of superficial Pt atoms, which can kill both cisplatin-sensitive/resistance cancer cells. Direct evidence in the oxidization of superficial Pt atoms is validated to observe the formation of platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Extant literature reports that cellular response to the cytotoxic agents (e.g., doxorubicin and cisplatin) includes life cycle inhibition or induction of death by apoptosis. Moreover, excessively high concentrations of such cytotoxic substances can induce cell death by necrosis [69][70][71]. The hybrid membrane-coated nanoparticle system-based specific internalization is expected to increase the intracellular concentration of drugs that might act synergistically to exhibit enhanced anticancer effects.…”
Section: In Vitro Therapeutic Effectmentioning
confidence: 99%
“…Extant literature reports that cellular response to the cytotoxic agents (e.g., doxorubicin and cisplatin) includes life cycle inhibition or induction of death by apoptosis. Moreover, excessively high concentrations of such cytotoxic substances can induce cell death by necrosis [69][70][71]. The hybrid membrane-coated nanoparticle system-based specific internalization is expected to increase the intracellular concentration of drugs that might act synergistically to exhibit enhanced anticancer effects.…”
Section: In Vitro Therapeutic Effectmentioning
confidence: 99%
“…Moreover, STEM images of the supernatants (Figure S4, Supporting Information) also suggested a disassembly of smaller nanoclusters (<5 nm) and/or metal ions from the Pt‐AuNS after efficient photothermal heating, which enabled the detection of a greater number of oxidized metallic species. [ 20 ] By contrast, NIR irradiation led to a variety of irregular and fragmented nanoparticles from the AuNS. The formation of larger sized Au nanoparticles may yield less activities in the subsequent reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary results implicated that MSNs-Pt have much higher therapeutic efficacy than PEG-MSNs-Pt in both in vitro and in vivo experiments. Likewise, it was demonstrated that nano-Pt triggered the autophagy and immunological responses in the tumor area [41]. These preclinical experiments are currently ongoing; we are focusing on the underlying molecular mechanisms of therapeutic effects rendered by MSNs-Pt with the nPtNP distributions on the different topological domains of MSNs, i.e., nPtNPs reduced on the MSN surface and surface/channels, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that PtNPs exhibit high catalytic activity, scavenging the singlet oxygen and superoxide to protect cells [36,37,38]. On the other hand, nanoparticulate Pt (nano-Pt) showed cisplatin-like function to inhibit cancer cell progression, cytotoxicity and less drug resistance [41]. Previous reports also used microwave-assisted methods to synthesize mesoporous silica aerogel-supported PtNPs (SAP) for a proton exchange membrane fuel cell [42].…”
Section: Discussionmentioning
confidence: 99%